2020
DOI: 10.3390/ijerph17207618
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota and Inflammation: An Overview

Abstract: The gut microbiota encompasses a diverse community of bacteria that carry out various functions influencing the overall health of the host. These comprise nutrient metabolism, immune system regulation and natural defence against infection. The presence of certain bacteria is associated with inflammatory molecules that may bring about inflammation in various body tissues. Inflammation underlies many chronic multisystem conditions including obesity, atherosclerosis, type 2 diabetes mellitus and inflammatory bowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
310
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 451 publications
(328 citation statements)
references
References 155 publications
(200 reference statements)
11
310
0
7
Order By: Relevance
“…Gut microbiota comprise a community of microorganisms which have many important functions for the health of their host (see other reviews [ 19 ]): they defeat invading pathogens, metabolize nutrients, produce neurotransmitters and regulate the immune system. During recent years, the crucial role of intestinal microbiota for the development of different diseases like infections, metabolic, autoimmune and mental diseases has been recognized [ 20 ].…”
Section: Altered Gut Microbiota In Alzheimer´s Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Gut microbiota comprise a community of microorganisms which have many important functions for the health of their host (see other reviews [ 19 ]): they defeat invading pathogens, metabolize nutrients, produce neurotransmitters and regulate the immune system. During recent years, the crucial role of intestinal microbiota for the development of different diseases like infections, metabolic, autoimmune and mental diseases has been recognized [ 20 ].…”
Section: Altered Gut Microbiota In Alzheimer´s Diseasementioning
confidence: 99%
“…Actually, recent studies showed an association of the development of neurodegenerative diseases like AD with alterations of the gut microbiota [ 19 , 21 ]. In fact, studies with AD patients and healthy controls conducted at the Alzheimer´s disease Research Center showed significant differences regarding the composition of the intestinal microbiome [ 22 ].…”
Section: Altered Gut Microbiota In Alzheimer´s Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Low-grade inflammation has been associated with a range of physical health conditions such as cardiovascular disease and diabetes [10,11]. Notably, a large body of work has associated low-grade elevations in CRP with cardiovascular events -however subsequent work has questioned the direction of causality in this relationship [12].…”
Section: Inflammation and Physical Health Disordersmentioning
confidence: 99%